The Labour Market Performance of Canadian Immigrants: The Role of Location of Oversea Degree and of Foreign Canadian Degree Holder's Place of Origin - Dong, Fang (Université d'Ottawa | University of Ottawa, 2016)
Will the highly skilled immigrants find jobs in Canada matching their income expectations and their training? With the Public Use Micro-data File (PUMF) of the 2011 National Household Survey (NHS), earning ability differences between Canadian and immigrant workers, from both Western and developing countries, are examined under two major effects: 1) place of highest degree; and 2) place of origin of the immigrants who received Canadian degrees. The effectiveness of Canadian and Foreign Education systems are tested based on the major fields of individuals’ highest degrees. The research finds that the Canadian labour market performances of immigrants are lower for those whose location of highest degree was outside Canada. Canadian education is effective on upgrading immigrant’s labour performance.